Risk factors and prognostic analysis of endometrial cancer with para-aortic lymph node metastasis - Feng Cheng; Li Yang; Qiang Wen; Jianying Xu; Feng Shao (Discover Oncology)
Abstract Background Assessment of lymph node involvement plays a pivotal role in the surgical staging of endometrial cancer (EC), offering essential prognostic information. In this study, we aimed to identify predictors of para-aortic lymph node metastasis, assess survival outcomes, and refine surgical strategies for lymphadenectomy in patients with EC. Methods A retrospective analysis was performed on 713 patients with endometrial cancer who underwent comprehensive staging surgery between July 2016 and July 2019. Clinical, pathological, and follow-up data were systematically collected. Univariate and multivariate logistic regression analyses were conducted to identify risk factors, and survival outcomes were evaluated using Kaplan–Meier analysis. Results Among 713 patients with endometrial cancer, lymph node metastasis was observed in 70 cases (9.8%), including 43 (6.0%) with para-aortic lymph node (PAN) involvement. Multivariate analysis identified LVSI, pelvic lymph node (PLN) metastasis, and elevated CA125 as independent predictors of PAN metastasis. Non-endometrioid histologies, particularly serous carcinoma, were associated with significantly higher PAN involvement. The 5-year survival rate for patients with PAN metastasis was 62.8%. Patients with isolated PAN metastasis (PLN − PAN+) had better 5-year OS (78.6%) than those with both PLN and PAN involvement (55.2%), though not statistically significant (log-rank P = 0.173). Conclusions Para-aortic lymph node (PAN) metastasis is rare in early-stage, low-risk endometrial cancer, and routine dissection may be safely omitted. However, para-aortic lymphadenectomy remains essential for patients with high-risk features, such as non-endometrioid histology, lymphovascular space invasion (LVSI), pelvic node metastasis, and elevated CA125 levels. Notably, uterine serous carcinoma is associated with frequent nodal spread and poor five-year survival.